Incidental Ectopic pancreas in gallbladder: a case report: Páncreas Ectópico incidental en vesícula biliar: reporte de caso - Zamora Gonzales, Pedro L. (2022)
Ectopic pancreas is an unusual finding, with an incidence below 0.5% of all reports worldwide. We report a 26 years old woman who went to emergency room with abdominal pain and underwent laparoscopic cholecystectomy. The pathology report described pancreatic ectopic tissue in the wall of the gallbladder. This finding must be thoroughly evaluated because this tissue can suffer diseases like pancreatitis, cystic tumours and malign degeneration, and should be considerated in the context of gallbladder polips with digestive sintomatology.